Effect of COVID-19 on Recreational Vehicle–related Injuries at a Level 1 Pediatric Trauma Center - Shengqing Wang, BA; Edward T. Lawson, MD; Lindsey N. Urquia, MD; Berkay Basagaoglu, MD; Purushottam Nagarkar, MD; Jennifer S. Kargel, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Recreational vehicle injuries in pediatric patients commonly involve extremity trauma requiring plastic surgery intervention. The primary purpose of this study is to delineate the demographic characteristics, clinical presentation, and outcomes of recreational vehicle–related injuries in children from a reconstructive surgery perspective with a focus on changes in incidence, patient characteristics, and outcomes during the COVID-19 lockdown period. Methods:. This is a retrospective analysis of pediatric patients aged 0–18 years who presented to our emergency department with recreational vehicle–related injuries necessitating plastic surgery evaluation between September 2017 and March 2022. Nonlimb injuries were excluded. The chi-square test, Fisher test, t tests, and interrupted time series were used to analyze for significant associations and differences between prepandemic and pandemic groups. Results:. There were 39 patients who met the inclusion and exclusion criteria. Most injuries involved the upper extremities (54%), and the most common pattern of injury was fracture with associated soft tissue defect (51%). The most common types of reconstructive operative interventions were free flaps or neurovascular grafting (36%). An 83% increase from 6 patients per year in 2019 to 11 patients per year in 2020 and 2021 was observed. There was a significantly higher number of reconstructive surgical interventions for patients in the pandemic group compared with the prepandemic group. Conclusions:. The incidence of injuries increased during the pandemic, and patients needed a significantly higher number of reconstructive surgical interventions during the initial hospital stay.